On the Impact of Response Patterns on Survey Estimates from Access Panels - Tobias Enderle; Ralf Münnich; Christian Bruch (Survey Research Methods, 2013)
Household and individual surveys increasingly gain importance in policy support and other areas. However, the raising number of surveys leads to reduced response rates. One way to overcome the problem of nonparticipation in surveys involving a non-response bias is to use access panels as a sampling frame. Though leading to expected higher response rates, the self-selection process at the recruitment stage urges the need for a bias correction. This can be done directly when extrapolating the estimates to the population of interest or when using response propensity scores. The latter implies a correct model specification on the recruitment stage.